Morphological and molecular investigation of Gomphonema longissimum and related taxa from Malili lakes (Indonesia) with comments on diatom evolution in ancient lakes. Issue 2 (2nd April 2020) - Kulikovskiy, Maxim; Kapustin, Dmitry; Glushchenko, Anton; Sidelev, Sergei; Maltsev, Yevhen; Gusev, Evgeniy; Kezlya, Elena; Shkurina, Natalia; Kuznetsova, Irina; Kociolek, Patrick
ABSTRACT: Four species of Gomphonema described by Hustedt with fusiform valve shape are studied for the first time using SEM. G. longissimum Hustedt, G. angustissimum Hustedt, G. woltereckii Hustedt and G. subtiliforme Hustedt were described, and are known only, from the ancient Malili lake system in Indonesia. Molecular investigations of two cultured strains of G. longissimum, using 18S rDNA and rbc L, are presented. In terms of morphology, these four species have unusually long valves and a fusiform shape otherwise unknown in Gomphonema, yet morphological similarities with other species include C-shaped or semi-circular areolae, uniseriate striae, pseudosepta, apical pore fields, a straight raphe with hooked internal proximal ends and a typical stigma in G. longissimum and G. angustissimum . Results of the molecular study support placement of G. longissimum with other 'typical' Gomphonema species. G. subtiliforme and G. woltereckii both lack a stigma. G. subtiliforme is similar in shape and morphology to members of the group G. subtile Ehrenberg, which all bear stigmata. G. woltereckii differs from G. longissimum and G. angustissimum by having areolae that are semi-circular, not C-shaped, and by the absence of a stigma. Therefore, based on morphology, we conclude these extraordinarily large Gomphonema taxa are similar to each other and generally resemble other species of the genus, yet there is enough variation in presence/absence of stigmata and structure of the areolae that they do not necessarily form a distinct group. Thus, despite their large size, and presence in the same lake system, we cannot conclude they form a species flock. Less than two dozen Gomphonema species are present in Malili lakes whereas some other ancient lakes, such as Lake Baikal, have many more species and exhibit species flocks.